BEHAVIOUR OF SOME WALNUT, HAZELNUT AND SWEET CHESTNUT CULTIVARS UNDER THE ENVIRONMENTAL CONDITIONS FROM SOUTH OF ROMANIA - Mihai Botu; Adina Vicol; Ion Botu; Silvia Preda; Gheorghe Achim; Andreea Giorgota (Fruit Growing Research, 2012)
The nut crops are important for their valuable fruits and for their potential to increase the economic growth of Romania. The Southern part of Romania which includes the regions of Oltenia and Muntenia is known for its favourable conditions for fruit growing and in particular for nut crops like walnut, hazelnut and sweet chestnut. During the last two decades at University of Craiova - SCDP Vâlcea several cultivars trials were set up in order to compare the Romanian and foreign cultivars and to establish the most favourable ones for culture in this part of the country. This study presents the behaviour of 19 walnut cultivars (9 Romanian ones and 10 of foreignorigin), 19 hazelnut cultivars (8 Romanian and 11 foreign ones) and 11 cultivars and hybrids of sweet chestnut (3 Romanian and 8 of foreign origin). Due to the results obtained several cultivars of walnut, hazelnut and sweet chestnut are recommended to be propagated and planted into the orchards from southern part of Romania.